Contingent Fit between Business Strategy and Environmental Uncertainty: The Impact on Tax Avoidance in Manufacturing Companies - Ellen Kiara; Elfina Astrella Sambuaga (Universitas Pelita Harapan, 2024)
The study aimed to examine the contingent fit level between business strategy and environmental uncertainty using tax avoidance with book-tax differences as the dependent variable, business strategy and environmental uncertainty as independent variables and included five types of control variables consisting of leverage, property, plant and equipment, inventory intensity, firm size and return on assets. The study used samples from manufacturing companies with a total sample of 510 observations from 2,050 observations for 5 years from 2015-2019 taken from S&P Capital IQ. The data processing carried out results from treatment using the Win so rize method with 5% on the dependent variable, namely BTD, and the control variable on ROA. The study's results prove that the contingent fit level between business strategy and environmental uncertainty has a negative and insignificant effect on tax avoidance. Meanwhile, environmental uncertainty has a positive and significant effect on tax avoidance.